Islam, Wanita dan HAM dalam Perspektif Hukum Islam (Analisis Kasus KDRT di Pengadilan Agama Medan) - Siregar, Rayani Hanum (UIN Sunan Kalijaga, 2009)
It is proper to thank the god that the law number 23/2004 on hardness abolition in household soon will be legislated as a constitution which will provide a protection for women, their safety and rights, men and children whom are being a hardness victim in household. This law had the same point with the law on human rights to live, to be not tortured, privacy freedom, thought and conscience as written in at law number 39/1999 verse 2.But, the authority that bonds the law is needed to be re-questioned, because that a lot of hardness chases raise among the society out of the civil law authority. There chase to chase rise among the society are which seems lying under the civil law authority. Practically, this law seems has lost its authority. This state arise an ambiguity about its law properness and the proper law to be applied. There are a lot of household hardness chases which areshould be the start point for the government and jurists to study furthermore the applying of law number 23/2004, because it is practically not used as reference law in Islamic court which managed the familial, marital and divorce affair. It is urgent to know that most of household hardness is raised from the familial and household matter.A simple research about household hardness with its relation with divorce affair registered to the Islamic court in Medan that the writer had worked indicated that more than 30% of the registered chases contain of household hardness. But because of the hardness matter is out of Islamic court authority made the authority of the law number 23/2004 is dilemma.